Fullerol–graphene nanobuds: Novel water dispersible and highly conductive nanocarbon for electrochemical sensing. (December 2017) - Bourlinos, Athanasios B.; Georgakilas, Vasilios; Mouselimis, Vasilios; Kouloumpis, Antonios; Mouzourakis, Eleftherios; Koutsioukis, Apostolos; Antoniou, Myrsini-Kyriaki; Gournis, Dimitrios; Karakassides, Michael A.; Deligiannakis, Yiannis; Urbanova, Veronika; Cepe, Klara; et al.
Graphical abstract: Highlights: Synthesis of water dispersible graphene–fullerol hybrid is presented. Graphene–fullerol hybrid is highly conductive with 0.8 × 10 5  S m −1 . Graphene–fullerol hybrid shows high aqueous dispersibility due to fullerol species. –OH/–O − groups in the fullerol structure promote electrochemical response. Abstract: The covalent functionalization of graphene enabling to overcome its hydrophobicity and still keeping a high conductivity is a challenging task, particularly for advanced biosensing applications. We present a facile strategy towards water dispersible nanocarbon with excellent conductive and sensing properties. Graphene–fullerol (GFL) covalent hybrid is prepared by impregnation of chemically exfoliated graphene sheets with fullerol clusters followed by thermal treatment. The partial dehydroxylation of fullerol during heating is necessary for exposing the fullerene skeleton to graphene and promoting their covalent bonding. The remaining hydroxyl and ionic groups equip the final product with good dispersibility in water (0.04 mg mL −1 ). Simultaneously, the GFL hybrid retains a high electrical conductivity of 0.8 × 10 5  S m −1, which is comparable to that of unmodified graphene. The conductive and hydroxyl-bearing derivative was successfully applied for electrochemical sensing of dopamine, hydroquinone (HQ), and catechol (C) using cyclic voltammetry. GFL modified electrodes exhibited simultaneous HQ and C detection at lower potentials compared to other nanosensors.